Perlindungan Pelaku Usaha Atas Kesepakatan Dagang Tarif Bea Masuk antara Indonesia dan Amerika Serikat Perspektif Maṣlaḥah ‘Āmmah - Alfira; Ramadhan, Muhammad (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2026)
This study aims to analyze import duty tariff policies within the framework of international trade between Indonesia and the United States and assess the extent to which these policies protect domestic businesses, particularly Micro, Small, and Medium Enterprises (MSMEs). Tariff policy, as a fiscal instrument, has two main functions: a budgetary function as a source of state revenue and a regulatory function as a tool for regulating and protecting the economy. However, tariff policy is not neutral because it is fraught with the interests of the state, the market, and businesses. The method used is normative juridical legal research with a statutory approach and a conceptual approach. The results show that tariff policies have a causal impact on market structure and the position of businesses. Appropriate policies can increase competitiveness, but disproportionate policies have the potential to weaken businesses, especially MSMEs, which are most vulnerable to the pressures of globalization. The analysis of the benefits of the common good shows that tariff policies do not fully meet the principles of justice (al-'adl), balance (tawāzun), and prevention of harm (lā ḍarar wa lā ḍirār). Therefore, an integration of fiscal policy, legal protection, and the principle of maṣlaḥah ‘āmmah is necessary in policy formulation. This integration is expected to create a tariff policy that is fair, proportional, and oriented towards the welfare of the wider community.